ECOLOGICAL STUDY AND BIRD DIVERSITY OF TAWA RESERVOIR AND ITS SURROUNDING AREAS OF HOSHANGABAD DISTRICT (MADHYA PRADESH) - PRAGATI JOSHI,; VINOY K. SHRIVASTAVA, (The Bioscan, 2012)
The avian diversity of Tawa Reservoir and its surrounding areas at Hoshangabad district was studied for a period of two years during January 2009 to December 2010. The Line Transect Method was used for bird survey. This area inhabits many residential and migratory bird species. This habitat attracted 74 bird species belonging to 33 families and 14 orders. Saxicoloides fulicata (Indian Robin), Passer domesticus (House Sparrow), Nectarinia asiatica (Purple Sunbird), Bubulcus ibis (Cattle Egret) Acridotheres tristis (Common Mayna), Turdoides Striatus (Jungle Babbler) were prominent residents and Ardea alba (Great Egret), Mesophoyx intermedia (Intermediate Egret), Pseudibis papillosa (Black Ibis), Threskiornis melanocephalus (Oriental white Ibis) Anthracoceros coronatus (Malabar pied Hornbill) were migratory uncommon species and Sturnus pagodarum (Brahminy Starling) Ammomanes phoenicurus (Rufus tailed Finch Lark) Eremopteris grisea (Ashy crowned Sparrow Lark ), Hirundo rustica (Barn Swallow) were migratory common species of the study area. Availability of food in different seasons, different type of vegetation, agricultural land, water availability in surrounding areas, field activities were favorable conditions observed for birds’ survival in this area. The determination of bird species will help in the evaluation and comparison of possible changes regarding the bird fauna in the future.